Highway engineering : pavements, materials and control of quality - Nikolaides, Athanassios (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
'Preface Highway engineering is the term that replaced the traditional term road engineering used in the past, after the introduction of modern highways. Highway engineering is a vast subject that involves planning, design, construction, maintenance and management of roads, bridges and tunnels for the safe and effective transportation of people and goods. This book concentrates on design, construction, maintenance and management of pavements for roads/highways. It also includes pavement materials since they are an integral part of pavements. It has been written for graduates, postgraduates as well as practicing engineers and laboratory staff and incorporates the author's 30 years of involvement in teaching, researching and practicing the subject of highway engineering. Advancements in pavement materials, design, construction, maintenance and pavement management and the globalisation of the market make it imperative for the highway engineer to be aware of the techniques and standards applied globally. One of the objectives of the book is to provide integrated information on the abovementioned disciplines of highway engineering. Another objective is to include in one book both European and American standards and practices (CEN EN, ASTM, AASHTO and Asphalt Institute). This would result in a more useful reference textbook to pavement engineering courses taught in European and American educational establishments. Another objective of this book is to provide a reference textbook to practicing pavement engineers and materials testing laboratory staff, working on countries employing European or American standards and techniques'--
Includes bibliographical references and index.
Keywords: Pavements